Correlation between T stage and lymph node metastasis in rectal cancer treated with preoperative chemoradiotherapy. (October 2022) - Kim, Seijong; Huh, Jung Wook; Lee, Woo Yong; Yun, Seong Hyeon; Kim, Hee Cheol; Cho, Yong Beom; Park, Yoonah; Shin, Jung Kyong
Background: Depth of tumor is a risk factor for lymph node metastasis in rectal cancer, but impact of yield pathologic T (ypT) stage on lymph node involvement in rectal cancer remains unclear. The aim of this study was to evaluate the correlation between ypT stage and lymph node metastasis. Methods: From January 2010 to December 2015, 602 patients who were diagnosed with rectal cancer and treated with neoadjuvant chemoradiotherapy (CRT) followed by radical operation were reviewed retrospectively. The correlations between ypT stage and lymph node status and survival were evaluated. Results: On pathology, 179 (29.7%) patients exhibited regional lymph node metastasis. Lymph node metastasis was seen in 8.5% of ypT0 patients, 20% of ypT1, 18.4% of ypT2, 47.5% of ypT3, and 27.3% of ypT4. Positive lymph node metastasis was correlated with ypT stage. In addition, the difference of lymph node metastasis in ypT stage subgroups was statistically significant ( p  < 0.001). Five-year disease-free survival was significantly different in the ypT stage subgroups (88.7% versus 86.7% versus 82.6% versus 64.7% versus 72.7%, p  < 0.001), as was 5-year overall survival (96.2% versus 90.0% versus 95.8% versus 80.0% versus 90.9%, p  < 0.001). Conclusion: YpT stage is associated with lymph node metastasis in rectal cancer treated with neoadjuvant CRT and radical operation, and ypT0 patients exhibited an 8.5% lymph node metastasis rate. Therefore, the decision for local excision or the watch-and-wait strategy for rectal cancer treated with neoadjuvant CRT and predicted to show a pathologic complete response should be considered with caution.